Relations between the absolute characteristics of the components of the different-type eclipsing binary systems - Karetnikov, V. G. (Одеські астрономічні публікації, 2017)
By using our compiled catalogues of the characteristics of 303 eclipsing binaries with the constant and variable orbital periods, we computed the «Mass-Luminosity», «Mass-Radius» and «Mass- Temperatures relationships. These relationships are analyzed, the coefficients vary from one type of the eclipsing systems to another. It is assumed that the changes of the coefficients are of the evolutionary origin. The sequence of the studied systems according to the ages of the components is proposed.